Pengaruh Kualitas Produk, Citra Merek dan Word Of Mouth terhadap Keputusan Pembelian Busana Muslim Queensland - Vinda Fatihah; Kristina Anindita Hayuningtias (SEIKO : Journal of Management & Business, 2022)
Abstract The rapid development of Muslim fashion has made many Indonesian people, especially Muslim women, interested in using comfortable and certainly contemporary Muslim fashion products. With so many enthusiasts for Muslim fashion products, it has an impact on the rise of local Muslim fashion brands in Indonesia. This study aims to find out how much influence product quality, brand image and word of mouth have on the purchasing decisions of Queensland Muslim fashion products. The study used quantitative methods by distributing questionnaires via google-form to respondents who had purchased Queensland Muslim fashion products at least once with a sample criterion of at least 17 years of age. The sampling technique used the purposive sampling method and obtained as many as 100 respondents. The analysis technique uses multiple linear regression analysis. The results of this study show that product quality and word of mouth have a positive and significant effect on purchasing decisions. While the brand image does not influence the decision of consumers to buy Queensland products. Keywords: Buying decision; Product Quality; Brand Image; Word Of Mouth